Construction of Zinc Oxide into Different Morphological Structures to Be Utilized as Antimicrobial Agent against Multidrug Resistant Bacteria. (16th September 2015) - Elkady, M. F.; Shokry Hassan, H.; Hafez, Elsayed E.; Fouad, Ahmed
Abstract : Nano-ZnO has been successfully implemented in particles, rods, and tubes nanostructures via sol-gel and hydrothermal techniques. The variation of the different preparation parameters such as reaction temperature, time, and stabilizer agents was optimized to attain different morphological structures. The influence of the microwave annealing process on ZnO crystallinity, surface area, and morphological structure was monitored using XRD, BET, and SEM techniques, respectively. The antimicrobial activity of zinc oxide produced in nanotubes structure was examined against four different multidrug resistant bacteria: Gram-positive ( Staphylococcus aureus and Bacillus subtilis ) and Gram-negative ( Escherichia coli and Pseudomonas aeruginosa ) strains. The activity of produced nano-ZnO was determined by disc diffusion technique and the results revealed that ZnO nanotubes recorded high activity against the studied strains due to their high surface area equivalent to 17.8 m 2 /g. The minimum inhibitory concentration (MIC) of ZnO nanotubes showed that the low concentrations of ZnO nanotubes could be a substitution for the commercial antibiotics when approached in suitable formula. Although the annealing process of ZnO improves the degree of material crystallinity, however, it declines its surface area and consequently its antimicrobial activity.